2021
DOI: 10.1097/pas.0000000000001788
|View full text |Cite
|
Sign up to set email alerts
|

Spread Through Air Spaces (STAS) in Non−Small Cell Lung Carcinoma

Abstract: Tumor spread through air spaces (STAS) is associated with locoregional recurrence in patients undergoing limited resection (LR) for non−small cell lung carcinoma (NSCLC). We hypothesized that the observation of STAS in both the initial LR specimen and the additional resection specimen from the same patient, processed using different knives, would provide evidence that STAS is an in vivo phenomenon contributing to locoregional recurrence. We retrospectively identified patients with NSCLC (9 adenocarcinoma, 1 sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
(85 reference statements)
0
12
0
1
Order By: Relevance
“…However, some scholars have questioned STAS, arguing that it is only the spread of tumor cell clusters caused by knife cutting during specimen processing, and called it "Spread Through a Knife Surface" [ 12 ]. Recently, more and more studies have shown that STAS is an in vivo phenomenon rather than an artifact caused by specimen handling procedures [ 13 , 23 , 24 ]. However, could this in vivo phenomenon be another manipulation artifacts, caused by preoperative invasive biopsy?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some scholars have questioned STAS, arguing that it is only the spread of tumor cell clusters caused by knife cutting during specimen processing, and called it "Spread Through a Knife Surface" [ 12 ]. Recently, more and more studies have shown that STAS is an in vivo phenomenon rather than an artifact caused by specimen handling procedures [ 13 , 23 , 24 ]. However, could this in vivo phenomenon be another manipulation artifacts, caused by preoperative invasive biopsy?…”
Section: Discussionmentioning
confidence: 99%
“…Among them, STAS is an important risk factor for tumor recurrence after surgery for stage I NSCLC [9][10][11]. However, the existence of STAS has also been questioned by many scholars, who believe that STAS may be an artifact of human manipulation due to spreading caused by knife cuts during specimen processing [12], although some studies have been conducted on the specimen retrieval process and confirmed that STAS is an in vivo phenomenon that exists preoperatively and is not a result of spreading caused by specimen processing [13]. Whether STAS is associated with preoperative invasive manipulation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in specimens of lung adenocarcinoma with STAS as the main histological pattern, it was observed that the area of floating tumor mass of STAS was not the area while the knife cutting through the main tumor. After Gross et al (34) found STAS in the first surgical resection (R0 resection), several tumor cell clusters could still be found in the air cavity of the normal lung tissue resected in the subsequent second surgery. Metovic et al (35) confirmed through a prospective study that there was no significant difference in the incidence of STAS between fresh tissues and formalin-fixed tissues, and there was no obvious dominant distribution of STAS in the air cavity of the lung parenchyma before and after the knife cut through the tumor.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of STAS in stage I NSCLC reported in previous studies ranged from 14.8% to 55.4% [ 4 , 11 ]. As the understanding of STAS has improved, many studies have shown that STAS is an in vivo phenomenon rather than an artefact of specimen handling procedures [ 12 , 13 ]. Therefore, there is a growing interest in the diagnosis of STAS.…”
Section: Discussionmentioning
confidence: 99%